Native mycorrhizal fungi improve milkweed growth, latex, and establishment while some commercial fungi may inhibit them. Issue 5 (26th May 2022) - Koziol, Liz; Schultz, Peggy A.; Parsons, Sheena; Bever, James D.
Abstract: Arbuscular mycorrhizal (AM) fungi are root symbionts that can facilitate plant growth and influence plant communities by altering plant interactions with herbivores. Therefore, AM fungi could be critical for the conservation of certain rare plants and herbivores. For example, North American milkweed species are crucial hosts for monarch butterflies ( Danaus plexippus ). Understanding how mycorrhizal composition affects milkweeds will have direct impacts on the conservation and restoration of both increasingly threatened guilds. We present data from three studies on the effect of AM fungal composition on milkweed growth, latex production, and establishment. First, we grew seven milkweed species with and without a mixture of native mycorrhizal fungi. We assessed how important fungal composition is to milkweed growth and latex production by growing four milkweed species with seven fungal compositions, as single‐species inoculations with four native fungi, a mixture of native fungi, a single commercial fungus of presumably non‐native origin, and noninoculated controls. Finally, we assessed the field establishment of two milkweed species with and without native mycorrhizal inoculation. Milkweed species grew 98% larger and produced 82% more latex after inoculation with native mycorrhizae. Milkweeds were strongly affected by fungal composition; milkweeds were inhibited by commercial fungi (average of −14% growth) and showed variable but positive responses to native fungal species (average of +3% to +38% biomass). Finally, we found that restoration establishment was dependent on inoculation with native fungi and milkweed species. Overall, our findings indicate that some milkweed species (i.e., Asclepias syriaca and A. incarnata ) are not responsive to mycorrhizal fungal presence or sensitive to mycorrhizal composition while others are, including endangered species ( A. meadii ) and species of high conservation value ( A. tuberosa ). We conclude that the reintroduction of native AM fungi could improve the establishment of desirable milkweed species and should be considered within strategies for plantings for monarch conservation.